Factors associated with preterm delivery and low birth weight: a study from rural Maharashtra, India - Ahankari, Anand; Bapat, Sharda; Myles, Puja; Fogarty, Andrew; Tata, Laila (F1000Research, 2017)
Background: Although preterm delivery and low birth weight (LBW) have been studied in India, findings may not be generalisable to rural areas such as the Marathwada region of Maharashtra state. There is limited information available on maternal and child health indicators from this region. We aimed to present some local estimates of preterm delivery and LBW in the Osmanabad district of Marathwada and assess available maternal risk factors.